Analisis Komparatif Kualitas Pelayanan pada Minimarket Indomaret dan Alfamaret di Wilayah Perumnas Karawang - Robby Fauji; Sihabudin; Yulianti Sartika (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The world of marketing in the current era has changed rapidly, moving from traditional concepts to modern ones. Therefore, business people and businesses should be able to adapt to the dynamics of market developments and be able to produce innovative ideas that can attract consumer attention to their products. Population growth rates also influence the actions companies must take. The size of the community's needs is also influenced by the ever-increasing population growth rate, such as Alfamart and Indomaret Perumnas Karawang. This study aims to find out the comparison of the determination of the five research variables related to service qualifications between Alfamart and Indomaret perumnas Karawan by applying a type of comparative research and involving 100 respondents who shop at Alfamart and Indomaret perumnas Karawang. By applying quantitative research techniques, namely collecting data through the use of questionnaires and then displaying it in descriptive statistics. The findings of this study indicate that there are important variations among five service quality factors: tangibles, empathy, responsiveness, assurance, and reliability.